Recent advances in the use of vibrational chiroptical spectroscopic methods for stereochemical characterization of natural products - Batista, João M.; Blanch, Ewan W.; Da Silva Bolzani, Vanderlan [UNESP] (Royal Society of Chemistry (RSC), 2015)
Covering: 2000 to 2014 This review covers conformational and configurational assignments in natural product molecules using chiroptical spectroscopy reported over the last 15 years. Special attention is given to vibrational optical activity methods associated with quantum mechanical calculations.